2002
DOI: 10.1002/jemt.10231
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic neurons in the mammalian ovary

Abstract: Mammalian ovarian function is under endocrine and neural control. Although the extrinsic innervation of the ovary has been implicated in the control of both ovarian development and mature function, it is now clear that, from rats to humans, the ovary is endowed with a network of intrinsic neurons displaying diverse chemical phenotypes. This article describes the presence of these intrinsic neurons in the ovary of different mammalian species, and discusses the possible functions that they may have in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 37 publications
(35 reference statements)
5
35
1
Order By: Relevance
“…The increase of dopamine might be assumed to be the result of the direct action of norepinephrine on the ganglionic receptors, which, through the SON, release neurotransmitters that have an impact on the intraovarian cells, which are capable of synthesizing dopamine (31). Further reasons for dopamine increase might be its liberation through the nervous terminals of the SON or a combination of both phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of dopamine might be assumed to be the result of the direct action of norepinephrine on the ganglionic receptors, which, through the SON, release neurotransmitters that have an impact on the intraovarian cells, which are capable of synthesizing dopamine (31). Further reasons for dopamine increase might be its liberation through the nervous terminals of the SON or a combination of both phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported ACh esterase-positive fibers in the ovary, production of ACh by granulosa cells, and involvement of the peripheral cholinergic muscarinic system in the control of the developing and mature rat ovary using in vivo experiments. These studies indicated that the richly innervated ovary contains cholinergic innervations [2,12,17,18,58]. Thus, we suggest that activation of the peripheral cholinergicmuscarinic system likely plays an important role in reproductive physiology.…”
Section: Discussionmentioning
confidence: 67%
“…It is not possible from our experiments to know, however, the source or location of these amines. LH may locally induce the release of catecholamines either from: i) the nervous terminals coming from the peripheral innervation (pool of catecholamines synthesized in the celiac ganglion or in the superior ovarian nerve terminals) [1]; ii) the intrinsic neurons of the ovary (structures from a network of neurons developed as a ganglion and located in the meso-ovarium and hilium and neurons mostly isolated in the cortex and medulla) [10]; or iii) a combination of both.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of intrinsic ovarian neurons in several mammalian species, including rats, has been demonstrated [7-9]. Among the neurotransmitters expressed in these cells are nitric oxide (NO), neuropeptide Y (NPY) and catecholamines [10]. The celiac ganglion is part of the sympathetic prevertebral chain possessing a great variety of specific receptors and neurotransmitters such as catecholamines, neuropeptides, and nitric oxide [3,11,12], and constitutes a modulation center in the pathway of the afferent and efferent fibers between the central nervous system and the ovary [2].…”
Section: Introductionmentioning
confidence: 99%